Adjuvanted-SARS-CoV-2 Spike Protein-Based Microparticulate Vaccine Delivered by Dissolving Microneedles Induces Humoral, Mucosal, and Cellular Immune Responses in Mice - Smital Patil; Sharon Vijayanand; Ipshita Menon; Keegan Braz Gomes; Akanksha Kale; Priyal Bagwe; Shadi Yacoub; Mohammad N. Uddin; Martin J. D’Souza (Pharmaceuticals, 2023)
COVID-19 continues to cause an increase in the number of cases and deaths worldwide. Due to the ever-mutating nature of the virus, frequent vaccination against COVID-19 is anticipated. Most of the approved SARS-CoV-2 vaccines are administered using the conventional intramuscular route, causing vaccine hesitancy. Thus, there is a need for an effective, non-invasive vaccination strategy against COVID-19. This study evaluated the synergistic effects of a subunit microparticulate vaccine delivered using microneedles. The microparticles encapsulated a highly immunogenic subunit protein of the SARS-CoV-2 virus, such as the spike protein’s receptor binding domain (RBD). Adjuvants were also incorporated to enhance the spike RBD-specific immune response. Our vaccination study reveals that a microneedle-based vaccine delivering these microparticles induced spike RBD-specific IgM, IgG, IgG1, IgG2a, and IgA antibodies. The vaccine also generated high levels of CD4+ and CD8a+ molecules in the secondary lymphoid organs. Overall, dissolving microneedles delivery spike RBD antigen in microparticulate form induced a robust immune response, paving the way for an alternative self-administrable, non-invasive vaccination strategy against COVID-19.